Pengaruh Pengembangan Karier dan Stres Kerja Terhadap Komitmen Organisasi dan Niat Berpindah - Aila Aila; Regina Deka Sofia (MES Management Journal, 2026)
Turnover intention is unavoidable for companies, where turnover intention influences employees' decisions to leave their workplace. Understanding the mechanisms of turnover formation can help companies maintain workforce stability. This study aims to determine the relationship between career development, organizational commitment, job stress, and employee turnover intention in the Jakarta area. This study uses a quantitative method with an associative descriptive design. Items are assessed using a 5-point Likert scale (1 = Strongly Disagree/STS to 5 = Strongly Agree/SS). It can be concluded that development has a positive effect on organizational commitment, job stress has a negative effect on organizational commitment, and development has no direct effect on intention. However, job stress has a positive effect on continuance intention. This study concludes that organizational commitment also mediates the effect of development on intention to leave. This study also found that commitment to the organization does not choose as a wave that explains the influence of stress on intention to originate. This study contributes with additional empirical evidence, companies are advised to manage work stress proactively, develop transparent career paths that are effectively communicated to the entire employee hierarchy, and provide fair performance-based rewards including financial incentives and non-material recognition are needed to increase loyalty.